P67 Is there a difference between the sleep physiology of obese and super obese patients?. (15th November 2016) - Rajhan, A; Michael, L; Bain, A; Thomas, A; Allen, M
Abstract : Introduction: Bariatric surgery is increasingly recommended for managing patients who are both obese and super obese (BMI ≥45 ref. WHO Classification). We have compared if there are physiological and subjective differences between patients in these two categories. Methods: Patients assessed for bariatric surgery were split into the super obese and obese group. Their physiological parameters including Apnoea Hypopnoea Index(AHI), Desaturation Index(ODI >4%) and subjective results i.e., Epworth Sleepiness Score(ESS) and STOPBANG Questionnaire were compared. Results: 111 patients assessed for bariatric surgery attended for limited sleep studies from a period between July 2013 to December 2014. 57 patients were obese (40 females) and 54 were superobese (37 females) and the results are tabulated below. (Table 1 ) The superobese patients had a higher AHI, ODI and time spent desaturated when compared to the obese patients. Conclusion: 1) There is more physiological derangement in the super obese patient group so greater caution is needed in the administration of anaesthetic to such patients. 2) Despite the physiological derangement, superobese patients were less sleepy based on their ESS, the reasons for which are not entirely clear.